The Association Between CTLA-4, CD80/86, and CD28 Gene Polymorphisms and Rheumatoid Arthritis: An Original Study and Meta-Analysis - Liu, Weixi; Yang, Zhicheng; Chen, Yan; Yang, Haoyu; Wan, Xiaoxian; Zhou, Xindie; Liu, Ruiping; Zhang, Yunkun (Frontiers in Medicine, 2021)
Abstract Background: Rheumatoid arthritis (RA) is related to several pivotal susceptibility genes, including cytotoxic T-lymphocyte-associated protein 4 (CTLA-4) and costimulatory molecule (CD80/CD86) genes. Although the connection between polymorphisms of CTLA-4 and CD86 genes in different populations of RA have been studied extensively, the results are controversial. Objective: To clarify the correlation in the Chinese Han population between CTLA-4, CD80/86, and CD28 gene polymorphisms, and RA susceptibility. Methods: A case-control study (574 RA patients and 804 controls) was conducted to determine the correlation between CTLA-4 rs231775 and rs16840252 gene polymorphisms, CD86 rs17281995 gene polymorphisms, and the risk of RA for the Chinese Han population. Furthermore, an additional meta-analysis, including three single nucleotide polymorphisms (SNPs) (CTLA-4 rs231775, CTLA-4 rs3087243, and CTLA-4 rs5742909) from 32 citations, including 43 studies, 24,703 cases and 23,825 controls was performed to elucidate the relationship between known SNPs in the CTLA-4 genes and RA for more robust conclusions. Results: The results showed that CTLA-4 rs231775 gene polymorphism decreased the RA risk (GA vs. AA, OR = 0.77, P = 0.025), whereas CTLA-4 rs16840252 and CD86 rs17281995 gene polymorphisms were not related to RA susceptibility. Stratification analyses by RF, ACPA, CRP, ESR, DAS28 and functional class identified significant associations for CTLA-4 rs231775 and rs16840252 gene polymorphisms in the RF-positive and RF-negative groups. A meta-analysis of the literature on CTLA-4 gene polymorphisms and RA risk revealed that the risk of RA was decreased by CTLA-4 rs231775 gene polymorphisms. Conclusions: The CTLA-4 rs231775 gene polymorphism decreased the risk of RA, whereas CTLA-4 rs16840252 and CD86 rs17281995 gene polymorphisms were not related to RA risk. A meta-analysis indicated that CTLA-4 rs231775 and rs3087243 gene polymorphisms decreased the risk of RA. To support these analytical results, additional clinical cases should be investigated in further studies.